The effect of modelling acoustic media in cavities of lightweight buildings on the transmission of structural vibrations. (15th January 2015) - Flodén, O.; Negreira, J.; Persson, K.; Sandberg, G.
Highlights: Acoustic media is modelled inside cavities of multi-storey wood buildings. Its effect on the transmission of low-frequency vibrations is investigated. It is concluded that it is necessary to include acoustic media in the models. Including air alone results in higher amplitudes and a more resonant system. Including also the insulation dampens the vibration amplitudes. Abstract: Determining the dynamic behaviour of lightweight buildings by means of finite element analyses requires models representing the geometry involved in great detail, resulting in systems having many millions of degrees of freedom. It is, therefore, important to avoid unnecessarily detailed models by carefully considering what is essential to include in the models and the level of details required for describing the phenomena of interest accurately. In the study presented here, it was investigated whether or not air and insulation in cavities of multi-storey wood buildings affect the transmission of low-frequency structural vibrations. It was concluded, by means of numerical studies, that including air and insulation in cavities, modelled as acoustic media, affects the transmission from a floor to the underlying ceiling and surrounding walls.